Electrical and mechanical properties of flexible multiwalled carbon nanotube/poly (dimethylsiloxane) based nanocomposite sheets. Issue 6 (December 2021) - Viannie, Leema Rose; Banapurmath, N.R.; Soudagar, Manzoore Elahi M.; Nandi, Anilkumar V.; Hossain, Nazia; Shellikeri, Ashwini; Kaulgud, Vinita; Mujtaba, MA; Khan, Sher Afghan; Asif, Mohammad
Abstract: In this study, the development of highly flexible polymer nanocomposite sheets using multi-walled carbon nanotube (MWCNT) in a poly (dimethylsiloxane) (PDMS) matrix has been presented. Solution processing technique was employed, and MWCNTs were dispersed in n-hexane, and PDMS is resulting in a homogenous dispersion (between 2 wt% and 10 wt%). Scanning electron micrograph (SEM) images show the distribution of MWCNTs within PDMS matrix, which form continuous conductive networks resulting in percolation threshold even at 2 wt% filler concentrations. The electrical conductivity of the fabricated nanocomposite sheets was found to be about 1.3–158.2 S/m. Samples with 2 wt% and 4 wt% filler concentrations exhibit excellent temporal stability both in ambient and vacuum conditions, with near-zero temperature coefficient of resistance. The nanocomposite sheets used for mechanical studies were made as per ASTM D-412-C standards. For an optimal filler concentration of 5.58 wt% can be observed with stiffness of 0.486 MPa, the tensile strength of 0.422 MPa, the electrical conductivity of about 39.5 S/m, and elongation up to 120%. Therefore, this filler concentration is most suited for fabricating flexible strain sensors with good conductivity and temporal stability. Graphical Abstract: ga1